Calcium-Dependent Ion Channels and the Regulation of Arteriolar Myogenic Tone - Jackson, William F. (Frontiers in Physiology, 2021)
Arterioles in the peripheral microcirculation regulate blood flow to and within tissues and organs, control capillary blood pressure and microvascular fluid exchange, govern peripheral vascular resistance, and contribute to the regulation of blood pressure. These important microvessels display pressure-dependent myogenic tone, the steady state level of contractile activity of vascular smooth muscle cells (VSMCs) that sets resting arteriolar internal diameter such that arterioles can both dilate and constrict to meet the blood flow and pressure needs of the tissues and organs that they perfuse. This perspective will focus on the Ca2+-dependent ion channels in the plasma and endoplasmic reticulum membranes of arteriolar VSMCs and endothelial cells (ECs) that regulate arteriolar tone. In VSMCs, Ca2+-dependent negative feedback regulation of myogenic tone is mediated by Ca2+-activated K+ (BKCa) channels and also Ca2+-dependent inactivation of voltage-gated Ca2+ channels (VGCC). Transient receptor potential subfamily M, member 4 channels (TRPM4); Ca2+-activated Cl- channels (CaCCs; TMEM16A/ANO1), Ca2+-dependent inhibition of voltage-gated K+ (KV¬) and ATP-sensitive K+ (K¬ATP) channels; and Ca2+-induced-Ca2+ release through inositol 1,4,5-trisphosphate receptors (IP3Rs) participate in Ca2+-dependent positive-feedback regulation of myogenic tone. Calcium release from VSMC ryanodine receptors (RyRs) provide negative-feedback through Ca2+-spark-mediated control of BKCa channel activity, or positive-feedback regulation in cooperation with IP3Rs or CaCCs. In some arterioles, RyRs are silent. In ECs, transient receptor potential vanilloid subfamily, member 4 (TRPV4) channels produce Ca2+ sparklets that activate IP3Rs and intermediate and small conductance Ca2+ activated K+ (IKCa and sKCa) channels causing membrane hyperpolarization that is conducted to overlying VSMCs producing endothelium-dependent hyperpolarization and vasodilation. Endothelial IP3Rs produce Ca2+ pulsars, Ca2+ wavelets, Ca2+ waves and increased global Ca2+ levels activating EC sKCa and IKCa channels and causing Ca2+-dependent production of endothelial vasodilator autacoids such as NO, prostaglandin I¬2 and epoxides of arachidonic acid that mediate negative-feedback regulation of myogenic tone. Thus, Ca2+-dependent ion channels importantly contribute to many aspects of the regulation of myogenic tone in arterioles in the microcirculation.